Trans transgender life stories from South Africa - Morgan, Ruth; Marais, Charl; Wellbeloved, Joy Rosemary (Jacana Media, 2009)
"With more than twenty original voices from the trans community in South Africa, this book is a journal of shared experiences for trans people and a fascinating point of departure for interested members of the general public. The contributors who 'transitioned, are transitioning or will transition', have all been actively involved in the process of making the book and have a great deal to say about their personal experiences of being transgender today. Their illuminating and touching life stories are complemented by the extraordinary photographs by renowned photographer, Robert Hamblin. Many of the stories collected here touch on the isolation that transgender people often feel in their communities. Transgender issues are a taboo subject for discussion, which are either ignored by the media, or covered in an invasive, insensitive and sensationalist way. The stories stress the need to provide accurate information, counter negative stereotypes, reduce discrimination, provide transgender people with honest representations of their lives, and offer visible, positive role models. This book brings us all a small step closer to a future where no young transgender person in South Africa grows up in isolation and despair"--Publisher's website.